The Effect of Dividend Policy and Corporate Governance on Company Value: The Role of Tax Avoidance Moderation in Manufacturing Companies - Santoso Chandra; Herman Ruslim (Politeknik Siber Cerdika Internasional, 2026)
Background: Corporate value reflects market assessments of managerial decisions and governance quality. While prior studies have examined determinants of firm value, the combined effects of dividend policy, leverage, gender diversity, and CEO compensation remain underexplored in Indonesia's non-cyclical consumer sector, particularly the moderating role of tax avoidance. Objective: This study investigates the effects of dividend policy, leverage, gender diversity, and CEO compensation on firm value (Tobin's Q) in non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX), and examines whether tax avoidance, proxied by the Cash Effective Tax Rate (CETR), moderates these relationships. Methods: A quantitative causal-comparative design was applied using panel data from 36 IDX-listed non-cyclical consumer companies over 2020–2024, yielding 180 firm-year observations. Purposive sampling was employed, and data were analyzed through panel data regression with the Fixed Effect Model (FEM), followed by Moderated Regression Analysis (MRA). Results: Gender diversity exerts a significant negative effect on firm value, suggesting that greater board diversity is associated with lower Tobin's Q. Tax avoidance significantly and positively moderates the relationship between gender diversity and firm value. Conversely, dividend policy, leverage, and CEO compensation show no statistically significant effects, either directly or in the moderated models. Conclusion: Governance dynamics and tax management outweigh traditional financial indicators in shaping firm value. Gender diversity negatively affects Tobin's Q, reflecting market skepticism toward uninstitutionalized board changes, yet tax avoidance positively moderates this relationship. The findings emphasize strategic tax management and sound governance as key drivers of corporate value.